Evaluasi Manajemen Aktif Kala III Persalinan di Rumah Bersalin Pangestu Bandung - Eti Sukmiati (STIKes Karsa Husada Garut, 2015)
This study aimed to describe the active management of the third stage of the implementation of appropriate standards in normal childbirth in the maternity hospital Pangestu Bandung. This study is a descriptive study. The data collected is of primary data, obtained from direct observation nonparticipant on the implementation of the active management of the third stage of labor. The samples were all over normal delivery. Results from 30 deliveries, on the implementation of the principle of active management of the third stage, namely: oxytocin less than 2 minutes was performed according to the standard, controlled cord stretching already standardized but there are some as much as 20% do not, wait for the uterus to contract in advance. And on the implementation of uterine massage after delivery of the placenta 16.7% have not done according to the standard. From these results it can be concluded that the overall implementation of the active management of the third rated well on the oxytocin and controlled cord stretching and massage of the uterus is considered less good.